2016
DOI: 10.1002/chem.201504846
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Earth Metal Zirconate Perovskites MZrO3 (M=Ba2+, Sr2+, Ca2+) Derived from Molecular Precursors and Doped with Eu3+ Ions

Abstract: The effect of alkaline earth metal alkoxides on the protonation of zirconocene dichloride was investigated. This approach enabled the design of compounds with preset molecular structures for generating high-purity binary metal oxide perovskites MZrO3 (M=Ba(2+), Sr(2+), Ca(2+)). Single-source molecular precursors [Ba4 Zr2 (μ6 -O)(μ3 ,η(2)-OR)8 (OR)2(η(2) -HOR)2 (HOR)2 Cl4], [Sr4 Zr2 (μ6 -O)(μ3 ,η(2)-OR)8 (OR)2 (HOR)4 Cl4], [Ca4 Zr2 (μ6-O)(μ3 ,η(2)-OR)8 (OR)2 Cl4], and [Ca6 Zr2 (μ2 ,η(2)-OR)12 (μ-Cl)2 (η(2) -HOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…It is generally considered that excluding halide ligands from precursors is advantageous for the formation of clean oxide materials, although several examples have now shown that post-calcination washing steps can remove any halide contaminants (which are often highly soluble) from the desired oxide phase. 12,26,83,89,91,92 Whilst it is difficult to straightforwardly collect the multitude of different SSPs into set categories, in the following sections we have attempted to group the literature examples into five major groupings of molecular SSPs, plus a group of extended framework precursors and a final section upon statistically mixed mixed-metal species.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…It is generally considered that excluding halide ligands from precursors is advantageous for the formation of clean oxide materials, although several examples have now shown that post-calcination washing steps can remove any halide contaminants (which are often highly soluble) from the desired oxide phase. 12,26,83,89,91,92 Whilst it is difficult to straightforwardly collect the multitude of different SSPs into set categories, in the following sections we have attempted to group the literature examples into five major groupings of molecular SSPs, plus a group of extended framework precursors and a final section upon statistically mixed mixed-metal species.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…Apart from this, in the range of 350–550 nm, feeble excitation peaks are observed that are ascribed to the f–f transitions of Eu 3+ . This implies that a high quantum efficiency of PL excitation originates from the trap level …”
Section: Resultsmentioning
confidence: 99%
“…Because the MD transition is stronger, it is confirmed that Eu 3+ ions must occupy the inversion symmetry site in the BaZrO 3 matrix. Because of the difference in the ionic sizes of Ba 2+ (135 Å), Zr 4+ (72 Å), and Eu 3+ (95 Å), it could be considered that Eu 3+ ions must occupy centrosymmetric Zr 4+ sites in the BaZrO 3 lattice. , The emission spectrum of Eu 3+ -doped samples shows some weak peak above 700 nm due to the f–f transition of the Eu 3+ ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] The preorganized metal À oxygen (alkoxy) bonds and the intrinsic reactivity against nucleophilic attack as well as the thermally labile nature of the organic periphery makes metal alkoxides ([M(OR) x ], [MM'(OR) x + y ]) as preferred starting materials for sol À gel and chemical vapor deposition processes. [2,[10][11][12][13][14][15][16] Metal-organic compounds in general enable low temperature processing of nanostructured oxides and their solid-solutions or composites that are challenging to obtain by traditional solid-state reactions.…”
Section: Introductionmentioning
confidence: 99%